Pengembangan Media Pop-Up Digital pada Materi Sistem Komputer - Farros Shaffira; Hakkun Elmunsyah; Mutilah Mutilah; Aqiqul Putra Zaibintoro (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study developed digital pop-up learning media for computer systems in the form of an interactive website to address passive learning caused by conventional slide-based instruction. The media integrates text, images, and pop-up effects across three subtopics: hardware, software, and brainware. Unlike some pop-up media that rely on QR code access, this media can be accessed directly through a website link. This study contributes feasibility evidence through expert validation and usability testing. Methods – This study used the Research and Development method with the 4D model, consisting of define, design, develop, and disseminate stages. The define stage included front-end analysis, learner analysis, and concept analysis. The design stage produced navigation structure and wireframe. In the develop stage, the website was validated by one material expert and one media expert using a 1-5 rating scale. In the disseminate stage, usability testing was conducted using the System Usability Scale (SUS) with 29 eighth-grade students. Findings – The material expert validation resulted in a score of 93%, categorized as “Very Good,” while the media expert validation resulted in a score of 87%, also categorized as “Very Good.” The SUS testing produced a mean score of 79.31, corresponding to grade “C” in relative standing and an adjective rating of “Good” in absolute usability. These two scales are not contradictory because they represent different interpretive frameworks. However, both indicate that the media has not yet reached the “Excellent” category.Research Implications – The developed media is feasible to be used as an alternative learning tool in Informatics, although improvements are still needed in interface consistency and usage guidance. This study involved only 29 students from one school, did not measure learning outcomes, and obtained verbal rather than written permission from the school. Future research should involve larger and more diverse samples, formal written permission, and experimental designs to examine the effectiveness of the media more rigorously.